Language and Culture: Kinship System of Lampung Sai Batin Ethnic - Amaliah; Patuan Raja; Ari Nurweni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Language, as an entity that binds human life, has the intention to convey something, perhaps the most complex and most interesting. Among the various languages in Indonesia, Lampung has unique and diverse greetings and is equipped with a set of rules for its use. However, although greetings in Lampung are very important as regional and national cultural assets that need attention and development, not many researchers have studied this. Therefore, this study aims to describe how the Lampung Sai Batin is created and used, especially addressing terms and to describe the use of addressing terms in the Lampung Sai Batin ethnic. The method used is a qualitative descriptive method with interview, observation and documentation through traditional figures of Sai Batin Kepaksian Pernong in West Lampung, Lampung. The study identified four main kinship groups: The Warei group, Apak Kemaman group, Adek Warei group, and the Children’s group. The findings reveal a strong relationship between language and culture, where kinship terms reflect social hierarchy, lineage, and cultural identity. Preserving this kinship system is important because it safeguards traditional values, strengthens intergenerational cultural transmission, and maintains politeness norms embedded in Lampung society. The study also discusses its implications and limitations.